Improving the Efficiency of Submersible Multistage Pumps Based on the Hydrophobization of the Flow Part Surfaces - G. A. Kromm; N. A. Drobnitsky; A. V. Volkov; A. A. Druzhinin; V. Y. Lyapin; A. V. Trulev; I. V. Kachanov; G. M. Brovka (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents an experimental study of an assembly of five stages of an electric centrifugal pump (ECP) installation, the flow part of which is modified according to the principles of biomimetics, namely using the “lotus leaf effect”. The object of the study was a 5A-35 ECP. The surfaces of the blade systems of impellers and guide devices of stages 5 A-35 were hydrophobized using the method of applying surfactant layers. The degree of impellers hydrophobicity was estimated by the wetting angle average value measured by three drops at three different points on the impeller surface. The impellers surface roughness under study was determined by the arithmetic mean profile deviation Ra and the profile height irregularities Rz. The issues related to the surfactant coating modification effect salt deposition and corrosion were studied. For this purpose, the surfaces of the original and modified impellers were subjected to intensive forced salt deposition as a result of prolonged exposure to saline solution. The conclusion about the samples corrosion resistance degree was made by changing their mass, which was due to the salt deposits formation during 15 hours of stay in solution, as well as using the drop method. Both methods have shown that the surfactant coating can serve as a salt deposition inhibitor, and the pump impeller modified by it has increased corrosion resistance. Thus, during comparative tests, a smaller mass of salt was deposited on the modified impeller sample during 15 hours of exposure in saturated saline solution than on the original sample. This indicates that the surfactant layer prevents the salt deposits fixation on the working surfaces of the pump stage. On the modified sample examined by the drop method, the indicator color changed in 20 minutes, and on the original one – in 2 minutes. Experimental studies have been carried out, during which the operation energy parameters of a five stages 5A-35 pumping package with initial and modified surfactant-coated impellers have been determined. The studies have shown a 2 % increase in efficiency in the pum-ping package of stages with modified impellers. The results of the study can be useful in the oil production, chemical industry, as well as in the housing and communal services sector.